Brazil-Africa technical cooperation in health: what's its relevance to the post-Busan debate on 'aid effectiveness'? - Russo, Giulliano (2021)
BACKGROUND Brazil is rapidly becoming an influential player in development cooperation, also thanks to its high-visibility health projects in Africa and Latin America. The 4th High-level Forum on Aid Effectiveness held in Busan in late 2011 marked a change in the way development cooperation is conceptualised. The present paper explores the issue of emerging donors' contribution to the post-Busan debate on aid effectiveness by looking at Brazil's health cooperation projects in Portuguese-speaking Africa. DEBATE We first consider Brazil's health technical cooperation within the country's wider cooperation programme, aiming to identify its key characteristics, claimed principles and values, and analysing how these translate into concrete projects in Portuguese-speaking African countries. Then we discuss the extent to which the Busan conference has changed the way development cooperation is conceptualised, and how Brazil's technical cooperation health projects fit within the new framework. SUMMARY We conclude that, by adopting new concepts on health cooperation and challenging established paradigms--in particular on health systems and HIV/AIDS fight--the Brazilian health experience has already contributed to shape the emerging consensus on development effectiveness. However, its impact on the field is still largely unscrutinised, and its projects seem to only selectively comply with some of the shared principles agreed upon in Busan. Although Brazilian cooperation is still a model in the making, not immune from contradictions and shortcomings, it should be seen as enriching the debate on development principles, thus offering alternative solutions to advance the discourse on cooperation effectiveness in health.